2019
DOI: 10.1016/j.jisa.2019.05.001
|View full text |Cite
|
Sign up to set email alerts
|

The language of biometrics: Analysing public perceptions

Abstract: There is an increasing shift in technology towards biometric solutions, but one of the biggest barriers to widespread use is the acceptance by the users. In this paper we investigate the understanding, awareness and acceptance of biometrics by the general public. The primary research method was a survey, which had 282 respondents, designed to gauge public opinion around biometrics. Additionally, qualitative data was captured in the form of the participants' definition of the term biometrics. We applied themati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 17 publications
3
20
1
1
Order By: Relevance
“…At the smallest side of the scale are those traits that respondents are not familiar with, gait palm print and signature which perhaps suggests that there is a lack of awareness around these characteristics which are further underlined by comparing the outcome of similar study. 47 The observations are also in agreement with earlier findings 48 on face and voice method. According to the researchers, they assert that not many people will like their pictures taken as in face recognition system or speak into a microphone as in voice recognition system due to privacy reasons.…”
Section: Respondent Characteristicssupporting
confidence: 90%
“…At the smallest side of the scale are those traits that respondents are not familiar with, gait palm print and signature which perhaps suggests that there is a lack of awareness around these characteristics which are further underlined by comparing the outcome of similar study. 47 The observations are also in agreement with earlier findings 48 on face and voice method. According to the researchers, they assert that not many people will like their pictures taken as in face recognition system or speak into a microphone as in voice recognition system due to privacy reasons.…”
Section: Respondent Characteristicssupporting
confidence: 90%
“…A 2019 poll of 4109 adults in the United Kingdom finds that 77% of respondents are uncomfortable with FRT being deployed by commercial companies, 49% support FRT use for policing purposes given appropriate safeguards, while 67% oppose it in schools and 61% oppose its use on public transport (Ada Lovelace Institute, 2019). Another survey using convenience sampling with 282 UK participants explored attitudes toward biometrics analysis overall and found that UK respondents were uniformly more comfortable with their biometric data being held by a government than a private company (Buckley and Nurse, 2019). For the United States, a Pew Research Center survey of 4272 adults found that acceptance varies for different types of FRT, depending on who is using the technology.…”
Section: Model Developmentmentioning
confidence: 99%
“…Idemudia and Raisinghani, 2014; Komiak and Benbasat, 2006). A survey with 282 UK participants on attitudes toward biometrics also finds that citizens are more accepting of technologies with which they are most familiar (Buckley and Nurse, 2019). Based on these studies, we derive the first two sets of hypotheses for our study: H1.1, H1.6 and H2.1, H2.3 (see Table 1).…”
Section: Model Developmentmentioning
confidence: 99%
“…It follows that the utilization of a biometric finger impression scanner can't be a solid and safe strategy of making installments or moving cash through digital financial services. The discoveries negate past research, which found that Buckley and Nurse (2019) seem to suggest that unique mark checking (bio metric) is a broadly utilized verification strategy in mobile banking.…”
Section: Reliabilitymentioning
confidence: 76%
“…Reliability can likewise be considered as a predictor variable in the reception and utilization of digital banking services that can be included in TAM system since client acknowledgment is the super basic part in the reception of innovation like mobile money services without which any innovation can be outdated so for this reason solid and secure technique can be consider like bio metric instrument for accomplishing the client trust and acknowledgment in online payments through cell phone. Buckley and Nurse (2019) appear to demonstrate that fingerprint scanning is a widely used authentication mechanism. Finally, a 2015 South Korean study found that consumers are more inclined to utilise methods that are less secure but easier to use, such as fingerprint scanning.…”
Section: Reliabilitymentioning
confidence: 99%